Pengaruh religiusitas terhadap gratitude pada remaja yang tinggal di panti asuhan Kristen - Agata, Winny; Sidabutar, Fransisca (Konsorsium Psikologi Ilmiah Nusantara, 2015)
Adolescents who live in the orphanage usually don’t live with their own family for a variety of reasons. Separation and disappointment with the family often make them hard to show gratitude. Previous studies show that there is a correlation between religiosity and gratitude. But even when they were educated in Christian orphanage that has a routine religious activity, many are found has a hard time to show his or her gratitude. By this research, author wanted to find out the influence of religiosity to gratitude, also the influence of each dimension of religiosity to gratitude. This study used The Four Basic Dimensions of Religiousness Scale and Gratitude Questionnaire – 6 Item Form. The participants of this study are 88 Christian adolescents who live at Christian orphanage, which are 11-20 years old. The result of this study shows that there is a significant influence of religiosity to gratitude (R2= .176, p= .003), with the most significant influence of religiosity’s dimension is behaving (B= .302, p= .019).